Building Resilience in Developing Countries Vulnerable to Large Natural Disasters. (Policy Papers; Policy Paper ;, 2019)
This paper discusses how countries vulnerable to natural disasters can reduce the associated human and economic cost. Building on earlier work by IMF staff, the paper views disaster risk management through the lens of a three-pillar strategy for building structural, financial, and post-disaster (including social) resilience. A coherent disaster resilience strategy, based on a diagnostic of risks and cost-effective responses, can provide a road map for how to tackle disaster related vulnerabilities. It can also help mobilize much-needed support from the international community.